Thrombosis in thrombocythemic Ph- myeloproliferations is associated with higher platelet count prior to the event: results of analyses of prothrombotic risk factors from a registry of patients treated with anagrelide - Schwarz, Jiří; Ovesná, Petra; Černá, Olga; Kissová, Jarmila; Maaloufová Soukupová, Jacqueline; Brychtová, Yvona; Doubek, Michael; Červinek, Libor; Cmunt, Eduard; Dulíček, Petr; Campr, Vít; Křen, Leoš; et al. (European journal of haematology, 2016)
Controversies still exist regarding definition of the thrombotic risks in Ph- (BCR/ABL1-) myeloproliferative disorders with thrombocythemia (MPD-T). Platelet counts at diagnosis are currently not taken as a risk factor of thrombosis. In our cohort of 1179 patients with MPD-T, prospectively registered for anagrelide treatment, we found that the median platelet count prior to the thrombotic event was significantly higher than at time points without any ensuing thrombosis (453 vs. 400 × 10(9)/L, P < 0.001), albeit higher platelet counts at diagnosis tended to be connected with fewer thrombotic events (in contrast to WBC counts at diagnosis). The JAK2(V617F) mutation predicted both arterial and venous events, while age >65 yr, hypertension, diabetes mellitus, smoking, elevated triglyceride and homocysteine levels predicted arterial events only. For venous events, the specific thrombophilic risk factors (factor V 'Leiden' and others), antiphospholipid antibodies, and elevated factor VIII levels played a major role. During anagrelide treatment (± aspirin), we documented a decrease in both venous (6.7-fold) and arterial events (1.8-fold), while bleeding (mostly minor events) increased twofold compared to history. Our results suggest that keeping platelet counts at low levels may be a meaningful therapeutic measure to prevent thrombosis, although their counts at diagnosis lack any prognostic value.
Keywords: myeloproliferative disorders; Thrombosis; thrombosis; bcr-abl fúzní proteiny; Mutation, Missense; Thrombocytosis; Fusion Proteins, bcr-abl; Male; missense mutace; Philadelphia Chromosome; Risk Factors; Aspirin; počet trombocytů; Janus kinasa 2; Janus Kinase 2; Aged; Prospective Studies; mužské pohlaví; senioři; registrace; trombóza; Amino Acid Substitution; trombocytóza; senioři nad 80 let; thrombophilia; lidé; JAK2; Platelet Count; ženské pohlaví; Humans; anagrelide; substituce aminokyselin; rizikové faktory; Aged, 80 and over; platelets; Registries; Quinazolines; filadelfský chromozom; chinazoliny; Female; prospektivní studie